P253 Evaluation of the ottawa COPD risk scale (OCRS) at royal stoke university hospital (RSUH), UK in predicting adverse outcome in COPD exacerbation. (12th November 2019) - Marathe, M; Oh, S; Leech, K; Stone, H; Hussain, I
Abstract : Background: The OCRS is a 10 point score designed to estimate short term adverse outcomes within 14 days (1). The score is made up of admission observations, investigations (including PCO2) and comorbidities. Adverse outcomes include death within 30 days, NIV/intubation, significant coronary events and early readmission. The aim of this project was to validate this score for the population at RSUH, UK and compare it to more established scores such as PEARL. Methods: We performed a retrospective review of 129 patients who presented to the emergency department at RSUH in December 2018. We used electronic records to calculate each patient's OCRS and determine the rate of adverse outcomes. We used the pre-existing BTS COPD audit forms to compare the patient's PEARL and DECAF scores. Results: Figure 1 shows the number of patients per score and the rate of adverse outcomes. 45 patients had no Arterial Blood Gas (ABG) and 42 patients had no electrocardiograms on admission. All 4 patients with OCRS score of 0 who had an adverse outcome had no ABG. The PEARL score gave a more useful estimation of readmission with 7% 30-day-readmission for PEARL score 0 – 1 and 40% 30-day-readmission for PEARL score 5 – 7. The 30 and 90 day readmission rates for the OCRS categories were calculated and showed no correlation. Discussion: Although the OCRS does seem to predict adverse outcomes in the highest scores (above 6), it does not help to differentiate between the lower scores. However, there are several limitations to this retrospective study including the inconsistent availability of admission ABGs, particularly in the lower risk groups. If this was available, a clearer risk stratification may have been possible. It is unclear however whether advocating ABGs during a busy acute take purely for the aim of risk stratification is justified. The PEARL score, which was designed to predict re-admission risk, was able to predict more successfully the 30 and 90 day readmission rates. We recommend using this score in supporting discharge and targeting resources aimed at reducing readmission.